Removal of a broken venous port from the pulmonary artery: a case series - Kutarski, Andrzej; Gozdek, Janusz; Stefańczyk, Paweł; Tułecki, Łukasz; Pietura, Radosław; Nowosielecka, Dorota (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2025)
The use of venous access ports carries a risk of complications, including catheter fracture with migration of catheter fragments into the pulmonary arteries. Experience in removing broken catheters is limited and there are no special tools. We present 4 cases of catheter removal using the available lassos/lasso catheter and tools designed for transvenous lead extraction and coronary sinus lead implantation via a femoral and subclavian approach. All four procedures were successful and without complications.